2012
DOI: 10.5536/kjps.2012.39.2.077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Raising Periods on Amino Acids and Fatty Acids Properties of Chicken Meat

Abstract: This study was to investigate the amino acid, free amino acid and fatty acid composition of chicken breast muscle and legs muscle by different raising periods (30, 36 and 42 days). In amino acid composition, the glutamic acids were 3.63% at 30 days, 3.63% at 36 days and 3.54% at 42 days in the breast muscle. The glutamic acid contents in the breast and leg muscle were decreasing tendency as raising periods increased. The total free amino acids were 370.6 mg at 30 days, 235.9 mg at 36 days and 246.3 mg at 42 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…Sourness was higher in the breast than in the thigh, irrespective of the type of chicken. Sourness in meat has been reported to be related to phenylalanine and isoleucine [32], and Chae et al [33] reported that phenylalanine and isoleucine levels were higher in the breast than in the thigh, supporting the findings of the present study. The saltiness was 6.9 in ST and 5.6-5.8 in the other meats.…”
Section: Changes In Organoleptic Characteristics Detected Using Electronic Tonguesupporting
confidence: 90%
“…Sourness was higher in the breast than in the thigh, irrespective of the type of chicken. Sourness in meat has been reported to be related to phenylalanine and isoleucine [32], and Chae et al [33] reported that phenylalanine and isoleucine levels were higher in the breast than in the thigh, supporting the findings of the present study. The saltiness was 6.9 in ST and 5.6-5.8 in the other meats.…”
Section: Changes In Organoleptic Characteristics Detected Using Electronic Tonguesupporting
confidence: 90%
“…닭고기는 고단백식품으로 불포화지방산이 다량 포함되어 있으며, 특히 닭다리살은 가슴살에 비해 다양한 생물학적 기능을 가지는 유리아미노산이 다량 포함되어 있으며 (Chae et al, 2012), 연하고 부드러운 식감을 가지고 있어 최근 1인 당 연간 소비량이 지속적으로 증가하는 추세이다 (Bonoli et al, 2007, Kim et al, 2016. 또한, 닭고기는 웰빙(well-being) 트렌드와 함께 닭발 젤라틴 분말과 밀식이유를 첨가한 재구 성 치킨육포 (Kim et al, 2012)에 관하여 선행연구가 이루어 졌으며, 노계 닭가슴살을 이용한 닭가슴살 햄 (Kim and Kim, 2016)의 이화학적 품질특성을 분석하여 닭고기 육제품의 부 가가치를 증진시킬 수 있는 연구 등이 활발히 이루어지고 있다.…”
Section: 서 론unclassified
“…Based on recent reports, comparing the quality of meat between broiler and Jidori chickens, it appears that the broiler has a higher Glu content than that of Jidori chicken, when the comparison was made at the marketable age of each strain (Goda, 2003;Matsuishi et al, 2005;Rikimaru and Takahashi, 2010;Yamada and Yamada, 2013). Because the content of Glu decreases with age in broiler chicken (Chow and Jacobson, 1968;Rikimaru and Takahashi, 2010;Chae et al, 2012), the difference in the content of Glu between broiler and Jidori chicken might be a reflection of their marketing age. Further, Wattanachant et al (2004) reported that Thai indigenous chicken had higher Glu content than the broilers.…”
Section: Other Chemical Substances Affect the Umami Characteristic Ofmentioning
confidence: 99%